2007
DOI: 10.1016/j.mineng.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Kimberlite degradation: The role of cation type

Abstract: It has been found that disintegration of kimberlite in contact with water is associated with the swelling of clays (such as smectite). This work investigates the possibility that cation exchange between kimberlite and the aqueous weathering medium could enhance or It is suggested that it may not only be swelling that determines the weathering behaviour of kimberlite but that the cations possibly influence the surface energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the presence of water these cations tend to hydrate, thereby forcing the clay layers apart in a series of discrete steps. The equilibrium process depends on the surface charge density or surface potential of the clay mineral, the type of exchangeable cations, particle content, the salt concentration, as well as the ratio of the cations in the bulk solution (Boek et al, 1995;Boshoff et al, 2007;Tombacz et al, 1989;Yildiz and Calimli, 2002;Yilmaz and Marschalko, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of water these cations tend to hydrate, thereby forcing the clay layers apart in a series of discrete steps. The equilibrium process depends on the surface charge density or surface potential of the clay mineral, the type of exchangeable cations, particle content, the salt concentration, as well as the ratio of the cations in the bulk solution (Boek et al, 1995;Boshoff et al, 2007;Tombacz et al, 1989;Yildiz and Calimli, 2002;Yilmaz and Marschalko, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…inorganic solutions (Boshoff et al, 2007;Morkel, 2006. Results showed that swelling clay minerals, especially the smectite species, were responsible for accelerating the breaking down of kimberlite material.…”
Section: Introductionmentioning
confidence: 99%
“…Kimberlite ores located in the vicinity of the South Africa-Zimbabwe border chiefly contain smectite and mica (Boshoff et al, 2007), which increased the viscosity of the suspension significantly (Burdukova et al, 2008a). The Chilean porphyry copper ores operated at Disputada plants contain mainly illite and chlorite as clay minerals which reduce the flotation rate of copper in all cases and increase copper losses in the tailings (Bulatovic et al, 1998).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…In clay science, cation exchange is an important factor influencing the clay-water interaction and cation exchange selectivity is one of the most important properties of 2:1 phyllosilicates. Since the equilibrium process of cation exchange depends on various factors, including surface charge density or surface potential of the clay mineral, the type of exchangeable cation, particle content, the salt concentration, as well as the ratio of the cations in the bulk solution (Boek et al, 1995;Boshoff et al, 2007;Tombacz et al, 1989;Yildiz and Calimli, 2002;Yilmaz and Marschalko, 2014), a complex system is needed to be established in order to understand the cation exchange process of bentonite. Corresponding equipment and methodologies should also be set up precisely from the perspective of clay science.…”
Section: Cation Exchange Of Bentonite In Electrolytes Solution Affectmentioning
confidence: 99%